Jewish and Christian self-definition ; v.3 - Meyer, Ben F.; Sanders, Ed Parish, 1937- (Philadelphia, PA Fortress, 1983)
Contents : v. 3 : Self-definition in the Greco-Roman world. Includes bibliographical references and indexes.
Keywords: Church history -- primitive and early church, ca. 30-600 -- addresses, essays, lectures; Judaism -- history -- Talmudic period, 10-425 -- addresses, essays, lectures